Capitalism 4.0 the birth of a new economy in the aftermath of crisis - Kaletsky, Anatole (New York, NY PublicAffairs, 2010)
In early 2009, many economists, financiers, and media pundits were confidently predicting the end of the American-led capitalism that has shaped history and economics for the past 100 years. Yet the U.S. economic model, far from being discredited, may be strengthened by the financial crisis. Argues that the economic recession of 2008-2009 forced a change in the philosophy of global capitalism, and will redirect the fundamentals of the capitalist system to create a new, successful, productive capitalism.
pt.1: Capitalism and evolution. Mr. Micawber and Mad Max -- Political economy and evolution -- The four ages of capitalism -- pt.2: The arrow and the ring. Annus Mirabilis -- The four megatrends -- The great moderation -- The financial revolution -- The ring of finance -- Boom and bust forever -- pt.3: Market fundamentalism self-destructs. The economic consequences of Mr. Paulson -- There is no can opener -- Toward a new economics -- pt.4: The great transition. The adaptive mixed economy -- Irresistible force meets immoveable object -- What - me worry? -- pt.5: Capitalism 4.0 and the future. Economic policy in capitalism 4.0 -- Politics in capitalism 4.0 -- Finance and banking in capitalism 4.0 -- The world of capitalism 4.0.
Keywords: Capitalism -- Philosophy; Economics -- Philosophy